2007
DOI: 10.1002/mnfr.200600285
|View full text |Cite
|
Sign up to set email alerts
|

Serum testing of genetically modified soybeans with special emphasis on potential allergenicity of the heterologous protein CP4 EPSPS

Abstract: Serum testing of genetically modified soybeans with special emphasis on potential allergenicity of the heterologous protein CP4 EPSPS" (2007). Faculty Publications in Food Science and Technology. 156.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…CP4 EPSPS protein did not bind significant quantities of IgE in soy-sensitive patients and there was no evidence for an increased allergenic potential of this biotech protein [41 ]. IgE binding pattern to extracts from genetically modified and wild type soybeans were found to be identical in western blotting experiments.…”
Section: Allergenicity Of Genetically Modified Soybeansmentioning
confidence: 96%
See 1 more Smart Citation
“…CP4 EPSPS protein did not bind significant quantities of IgE in soy-sensitive patients and there was no evidence for an increased allergenic potential of this biotech protein [41 ]. IgE binding pattern to extracts from genetically modified and wild type soybeans were found to be identical in western blotting experiments.…”
Section: Allergenicity Of Genetically Modified Soybeansmentioning
confidence: 96%
“…In a recent study, Hoff et al [41 ] determined the potential for developing allergic sensitization to the CP4 EPSPS protein in two different patient populations: children with atopic dermatitis and adult individuals with documented soy allergy and control groups. CP4 EPSPS protein did not bind significant quantities of IgE in soy-sensitive patients and there was no evidence for an increased allergenic potential of this biotech protein [41 ].…”
Section: Allergenicity Of Genetically Modified Soybeansmentioning
confidence: 99%
“…Recently, several reports have suggested that RuBisCO can be an allergen in other plants. [36][37][38] Another IgE binding protein identified in this study was ATP synthase. In one study, sequence homology was demonstrated between a bovine allergen and one of the subunits of ATP synthase which forms the basis for a potential cross-reactivity.…”
Section: Discussionmentioning
confidence: 97%
“…Immunoblots were conducted according to the previous protocol [49][50][51] with some modifications. In brief, the SDS-PAGE was conducted using 400 ng purified rhLF, bLF, hLF (kindly provided by professor Li Ning, Purity: 98%) and 10 μg protein extract prepared from a standard egg powder (Lot.…”
Section: Human Serum Testmentioning
confidence: 99%